2014
DOI: 10.1002/celc.201402147
|View full text |Cite
|
Sign up to set email alerts
|

From In Situ towards In Operando Conditions: Scanning Tunneling Microscopy Study of Hydrogen Intercalation in Cu(111) during Hydrogen Evolution

Abstract: We used electrochemical scanning tunneling microscopy to study the intercalation of hydrogen into a Cu(111) model electrode under reactive (in operando) conditions. Hydrogen evolution causes hydrogen intermediates to migrate into the copper lattice as function of the applied potential and the resulting current density. This H‐inclusion is demonstrated to be reversible. The presence of subsurface hydrogen leads to a significant surface relaxation/reconstruction affecting both the geometric and electronic struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
32
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 56 publications
2
32
1
Order By: Relevance
“…The reaction picture becomes increasingly complicated when considering that many of the studies cited above have reported severe surface reconstruction during CO 2 -reduction [244,285,287] (consistent with single crystal behavior [290,291]), which further complicates the common interpretation of their results. This lack of consensus concerning the exact nature and distribution of the reaction products extends to other works dealing with alternative, initially oxidized metals like Sn [292], Pb [293] or Au [294], in which product distributions unequivocally different from those observed on the corresponding reduced surfaces are reported but the stability is not specifically assessed.…”
Section: Catalyst-surface Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction picture becomes increasingly complicated when considering that many of the studies cited above have reported severe surface reconstruction during CO 2 -reduction [244,285,287] (consistent with single crystal behavior [290,291]), which further complicates the common interpretation of their results. This lack of consensus concerning the exact nature and distribution of the reaction products extends to other works dealing with alternative, initially oxidized metals like Sn [292], Pb [293] or Au [294], in which product distributions unequivocally different from those observed on the corresponding reduced surfaces are reported but the stability is not specifically assessed.…”
Section: Catalyst-surface Effectsmentioning
confidence: 99%
“…Surface mod f cat on.─ Extensive investigation of the electroreduction of CO 2 on AuCu alloys with different Au/Cu ratios has showed that their activity and selectivity compared to pure Au and Cu surfaces can be tuned by controlling the alloys' structural and electronic properties [290][291][292][293][294]. In particular, Au 3 Cu was found to have the highest mass activity for CO production [292], which was related to its enhanced ability to provide additional binding sites for *COOH while featuring weak *CO-binding (thus favoring its desorption as CO(g)) [297][298][299][300][301].…”
Section: Catalyst-surface Effectsmentioning
confidence: 99%
“…2,11 In addition to the debate over the presence of oxygen under reaction conditions, insitu scanning tunneling microscopy (STM) studies have indicated that copper surfaces are dynamic under reaction conditions. 12,13 Additional in-situ methods averaging over a macroscopic sample area can help to confirm and better understand these effects.…”
mentioning
confidence: 99%
“…1 Small shifts of peak centers (∆2θ ≈ −0.02 • ) were also observed during the reduction ( Figure S6), possibly reflecting hydrogen-induced expansion. 13 In this study, we used in-situ grazing-incidence X-ray diffraction (GIXRD) to examine changes in the surface composition and morphology of polycrystalline copper under CO reduction conditions. We showed that the Cu 2 O(111) diffraction peak disappears during the cathodic scan at about 0.3 V vs RHE while the Cu(111) peak simultaneously increases to its maximum intensity, with no further increase at more cathodic potentials, demonstrating 6 that the oxide is fully reduced to the metallic phase at potentials relevant to CO reduction.…”
mentioning
confidence: 99%
“…Just like for experiments, the amorphous nature of the interface means that, when working with periodic boundary conditions to well describe the metallic nature of the electrode and the liquid nature of the electrolyte, large systems need to be simulated to avoid spurious periodicity and thus simulationinduced crystallinity. Furthermore, the electrode surface might reconstruct in reaction conditions (15). Even in the absence of reconstructions, the dynamics at the interface tend to be orders of magnitude slower than in solution, so the necessary simulations to reach equilibrium are computationally expensive (16)(17)(18).…”
mentioning
confidence: 99%